Evaluation of frequency tracking methods. - Thomas, D.W.P (IEEE Transactions on power delivery)
This paper presents an analysis of proposed methods for tracking the fundamental power frequency to see if they have the performance necessary to cope with the requirements of future protection and control equipment and are robust enough to cope with the more demanding nature of modern power system conditions. The analysis shows that the linear estimation of phases, decomposition of single phase into orthogonal components and discrete Fourier transform perform extremely well but they all suffer from a periodic error in the estimated frequency if it departs from the assumed frequency. This can be cancelled using a low pass filter although it would introduce delays and obscure any real oscillations in the fundamental frequency. Alternatively, averaging over three phases could be used but higher harmonics in the oscillation of the estimation would be present